2008
DOI: 10.1136/bjsm.2007.044487
|View full text |Cite
|
Sign up to set email alerts
|

The practice of primary care sports medicine in the USA

Abstract: Salary can be related to age, gender, number of patients seen, and practice ownership. No statistical difference among salaries was found between MDs and DOs, osteopathic manipulative therapy (OMT) practice, region of the country, or how practices are marketed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A study conducted in 2006 reported that 58.3% of surveyed family physicians holding a sports medicine certificate of added qualifications (CAQ) were in private practice, and 41.7% practiced in an academic setting; 31.5% of these physicians practiced sports medicine only, while 22.1% reported practicing both sports medicine and family medicine. 2 Using demographic data reported by family physicians applying for the American Board of Family Medicine (ABFM) Sports Medicine CAQ examination from 2005 to 2015, we sought to understand the amount of time family physicians who are certified in sports medicine spend practicing sports medicine. Applicants supplied responses to the request to provide the "percentage of your practice involving sports medicine."…”
mentioning
confidence: 99%
“…A study conducted in 2006 reported that 58.3% of surveyed family physicians holding a sports medicine certificate of added qualifications (CAQ) were in private practice, and 41.7% practiced in an academic setting; 31.5% of these physicians practiced sports medicine only, while 22.1% reported practicing both sports medicine and family medicine. 2 Using demographic data reported by family physicians applying for the American Board of Family Medicine (ABFM) Sports Medicine CAQ examination from 2005 to 2015, we sought to understand the amount of time family physicians who are certified in sports medicine spend practicing sports medicine. Applicants supplied responses to the request to provide the "percentage of your practice involving sports medicine."…”
mentioning
confidence: 99%
“… 7 , 26 Last, a more recent emergence of sports medicine, especially with the advancement of surgical techniques, arthroscopy, rehabilitation measures, and favorable functional outcomes, potentially contributes to its development and sustainability in terms of income and private sector involvement. 9 Gaskill et al 12 investigated the financial return of orthopaedic fellowship training by estimating the net present value, internal rate of return, and break-even points and found sports medicine to be one of the specialties yielding positive returns. Morrell et al 20 demonstrated an increase in job opportunities available for fellowship-trained orthopaedic surgeons as compared with non–fellowship trained counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…7,26 Last, a more recent emergence of sports medicine, especially with the advancement of surgical techniques, arthroscopy, rehabilitation measures, and favorable functional outcomes, potentially contributes to its development and sustainability in terms of income and private sector involvement. 9 Gaskill et al 12…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
“…https://pubmed.ncbi.nlm.nih.gov/20 063220/ for men to be $40,000 greater than their women counterparts. 41 In the MIT Science Policy Review, Kong et al recommends four steps for opposition of gender discrimination within institutions. These include investing in early education initiatives for increasing female representation, instituting stronger state and federal policies around gender discrimination, fostering workplace practices that promote diversity and developing better quantification and metrics for assessing gender discrimination to enact more meaningful policies.…”
Section: The Perry Initiativementioning
confidence: 99%